Simultaneous Treatment of Osteochondral Lesion Does Not Affect the Mid- to Long-Term Outcomes of Ligament Repair for Acute Ankle Sprain: A Retrospective Comparative Study with a 3–11-Year Follow-up - Du, Ming-Ze; Su, Tong; Jiang, Yan-Fang; Jiao, Chen; Guo, Qin-Wei; Hu, Yue-Lin; Jiang, Dong (Frontiers in Surgery, 2022)
Purpose: To evaluate the mid- to long-term outcome of concurrent arthroscopic treatment of osteochondral lesion (OCL) and open anatomical repair of lateral ankle ligaments for severe acute ankle sprain patients and compare them to the outcome of those without OCL. Methods:166 patients with grade III acute lateral ankle ligament injuries underwent concurrent ankle arthroscopy and open anatomic ligament repair. 43 patients (group A) with OCL underwent arthroscopic treatment followed by open ligament repair. 105 patients (group B) without OCL were followed up as control. The evaluation parameters included sports recovery, post-operative visual analog scale (VAS) pain score, American Orthopaedic Foot and Ankle Society (AOFAS) score, Tegner score, sprain recurrence, satisfaction, and range of motion (ROM). Patients in group A were then subgroup analyzed according to age, sex, body mass index (BMI), injury side, OCL location and stage (Ferkel and Cheng’s staging system). Results: The postoperative exercise level of the two groups recovered to more than 90% of the normal level (91.2% ± 11.2% in group A and 90.9% ± 13.3% in group B, n.s.). The average time of group A and group B to return to pre-injury sports activity was respective 4.4 ± 1.0 months and 4.4 ± 1.2 months with no significant difference (p =0.716). No significant difference was found about the pre-operation VAS pain score, AOFAS score, and Tegner score between the two groups. The post-operative VAS pain score in group A were significantly higher than group B (0.8 ± 1.7 vs 0.3 ± 0.8, p = 0.027), but the difference was not clinically important. The postoperative VAS pain score of patients with stage D-F was significantly higher than that of patients with stage B-C (1.3 ± 2.1 vs 0.3 ± 0.9, p = 0.038). Conclusions: For the severe acute ankle sprain combined with OCL, the simultaneous arthroscopic treatment and open lateral ankle ligament repair achieved good mid- to long-term outcome. Except that the pain was more pronounced than the control group, there were no differences in other outcomes. Postoperative pain was positively correlated with the grade of OCL.